Game-based approach for modeling dialectical analysis - Cecchi, Laura (2001)
The operational semantics of defeasible logic programming (justification process) is based on a dialectical analysis of arguments and counterarguments. In [Abramsky, 1997] and [Abramsky(b), 1997], a game semantics is introduced in order to model a computation as a game between two players: the System and the Environment. The main idea is to use a game to model the interaction between the participants. The justification process can be seen as a game where a player proposes an argument for a goal q and tries to defend it while the other player tries to find counterarguments that defeat it. Therefore we can model a dialectical system through the interaction between two players: proponent and opponent. The purpose of this paper is to introduce a model based on a game structure for the operational semantics of Defeasible Logic Programming. The declarative semantics introduced, models the justification process when there exists a preference relation between contradictory arguments such that given two contradictory arguments it always determines which one is better.